Impact of climate change on the Himalayan alpine treeline vegetation - Sandeep Kumar; Vinod Prasad Khanduri (Heliyon)
The Himalayan alpine treeline varies depending on altitude and aspects, supporting a variety of plant species. In recent years, climate changes have exerted pressure on the vegetation in this region, challenging its adaptation to rapidly changing environmental conditions. This systematic review commenced by formulating a research question on the impact of climate change on Himalayan alpine treeline vegetation and conducted a thorough literature search, adhering to the PRISMA protocol. The rising temperatures, altered precipitation patterns, and other climate-related factors have initiated an upward shift in the treeline that threatens the unique biodiversity of the region. Indeed, in various parts of the Himalayas, there is evidence of the treeline moving upwards, altering plant regeneration and growing season, and impacting soil properties. There is a shift of vegetation ranging from 0.80 to 503.00 m in Himalayan treeline regions have been reported in various studies. Abies spectabilis and Betula utilis are the most sensitive, showing the highest upward shifts due to climate change. The repercussions of climate change on the Himalayan alpine treeline are anticipated to have significant ecological implications. Most species at the Himalayan alpine treeline exhibit poor regeneration status, while some others reveals good, fair, or no regeneration. Consequently, new regeneration patterns are emerging. Changes in soil temperature and physicochemical properties due to climate warming are ultimately affecting Himalayan alpine treeline vegetation. Additionally, shifts in the growing season and phenophases of various tree species have also been observed. The profound and far-reaching impacts of climate change on the Himalayan alpine treeline necessitates implementing mitigation and adaptation strategies to safeguard the delicate alpine ecosystems of the region.